HUBUNGAN SELF EFFICACY DENGAN PERILAKU SELF CARE PASIEN PASCA STROKE DI RUMAH SAKIT ISLAM SURABAYA - Ismatika Ismatika; Umdatus Soleha (Universitas Nahdlatul Ulama Surabaya, 2017)
The post-stroke can be regarded as the most difficult time for patients with post-stroke, they will experience a disability and inability to move as usual so that they will have difficulty in self care. The research was purposed to analyze the relationship of self-efficacy with self-care behavior of patients with post-stroke Islamic Hospital A Yani Surabaya. This study design was analytic correlation with cross sectional approach. The population of 36 people and a large sample of 36 respondents using purposive sampling technique. The independent variable of this research is self-efficacy and the dependent variable was self care behaviors. Instruments of research using questionnaires. Data analysis using the chi square test, significance value of α = 0.05. The results showed that the majority of the 36 respondents, or 26 respondents (72.2%) had good self efficacy and mostly or 27 respondents (75%) had good self-care behaviors. The results of statistical test Chi Square ρ = 0.03 <α = 0.05 showed relationship between self-efficacy with self-care behavior of patients with post-stroke. The better self efficacy post-stroke patients, the better self-care behavior. Post-stroke patients should be able to prepare and improve the behavior of self care, so that patients can independently live aww life in the social environment well. The role of nurses in improving self-efficacy by preparing the skills, motivation and health education about self care.